2019
DOI: 10.2298/hemind181009010s
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the acidic effluent from a copper smelter by flotation tailings

Abstract: Since commissioning in 1961, the copper mine Majdanpek, a part of the Mining and Smelting Complex Bor (RTB Bor), produced approximately 378 million tons of flotation tailings. Semiquantitative mineralogical analysis of the flotation tailings revealed significant content of carbonate minerals (approximately 20-25 %), indicating high acid neutralization capacity. Also, approximately 70 % of copper is in the form of the oxide mineral cuprite (Cu 2 O). Copper can be easily leached from cuprite by using sulphuric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results suggest a linear relationship between copper dissolution and temperature and a chemically regulated dissolution rate of the copper minerals. Other authors have similarly found rapid dissolution of Cu (85% of the total) from Cu oxide minerals within the first 5 min of sulfuric acid leaching [13].…”
Section: Alkaline Bioleachingmentioning
confidence: 77%
See 1 more Smart Citation
“…The results suggest a linear relationship between copper dissolution and temperature and a chemically regulated dissolution rate of the copper minerals. Other authors have similarly found rapid dissolution of Cu (85% of the total) from Cu oxide minerals within the first 5 min of sulfuric acid leaching [13].…”
Section: Alkaline Bioleachingmentioning
confidence: 77%
“…Semiquantitative mineralogical examination of the flotation waste revealed a considerable concentration of carbonate minerals (about 20-25%), indicating a high capacity for acid neutralization, and about 70% of the copper is contained in the oxide mineral cuprite (Cu 2 O) [13]. Acid leaching usually produces alumina and silica gels, which cause serious technical and environmental problems, especially in solvent extraction.…”
Section: Alkaline Bioleachingmentioning
confidence: 99%